What's the score? : 25 years of teaching women's sports history - Morris, Bonnie J., 1961- (Bloomington, Indiana : Red Lightning Books, 2022)
"Who is the first female athlete you admired? Were male and female athletes treated differently in your high school? Is there a natural limit to women's athletic ability? How has Title IX opened up opportunities for women athletes? Every semester since 1996, Bonnie Morris has encouraged students to confront questions like these in one of the most provocative college courses in America: Athletics and Gender, A History of Women's Sports. What's the Score?, Morris's energetic teaching memoir, is a peek inside that class and features a decades-long dialogue with student athletes about the greater opportunities for women-on the playing field, as coaches, and in sports media. From corsets, to segregated schoolyards, to the WNBA, we find women athletes the world over conquering unique barriers to success. What's the Score? is not only an insider's look at sports education but also an engaging guide to turning points in women's sports history that everyone should know"--
Timeline: 101 turning points in women's sports history -- Prologue: the bus ride before the game-or, a parable about our low expectations for -- Women's sports knowledge -- Introduction: nothing better to do on a Friday night? -- The strength of our foremothers: engaging students with the past -- How female athletes disappear: headlines, publicity, and media activism -- Tomboy identities, muscular ideals: discussing gender roles and homophobia in sports -- From half-court to federal court: title IX and the American playing field -- Global encounters with women's sports: teaching students at sea -- Challenges for a women's sports professor: evaluating twenty-fve years of class -- Conclusion: when the scoreboard went dark in 2020 -- Critical thinking resources.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 24, 2022).
JSTOR
Keywords: Morris, Bonnie J., -- 1961-; Morris, Bonnie J., -- 1961-; Sports for women -- History; Sports -- Sex differences; Sex discrimination in sports; Women college teachers -- United States -- Biography; Sports féminins -- Histoire; Sports -- Différences entre sexes; Discrimination sexuelle dans les sports; Professeures (Enseignement supérieur) -- États-Unis -- Biographies; History; Sports; BIOGRAPHY & AUTOBIOGRAPHY; Personal Memoirs; Health & Sexuality; Teaching Methods & Materials; EDUCATION; Physical Education; Women's Studies; SOCIAL SCIENCE; Coaching; SPORTS & RECREATION; Sex discrimination in sports; Sports for women; Sports -- Sex differences; Women college teachers; United States; Electronic books; Biographies; History